Characteristics and Global Occurrence of Human Pathogens Harboring Antimicrobial Resistance in Food Crops: A Scoping Review - Brunn, Ariel; Kadri-Alabi, Zaharat; Moodley, Arshnee; Guardabassi, Luca; Taylor, Phil; Mateus, Ana; Waage, Jeff (Frontiers in Sustainable Food Systems, 2022)
Background: The role of the crop environment as a conduit for antimicrobial resistance (AMR) through soil, water, and plants has received less attention than other sectors. Food crops may provide a link between the agro-environmental reservoir of AMR and acquisition by humans, adding to existing food safety hazards associated with microbial contamination of food crops. Objectives: The objectives of this review were: 1) to use a systematic methodology to characterise AMR in food crop value chains globally, and 2) to identify knowledge gaps in understanding exposure risks to humans. Methods: Four bibliographic databases were searched using synonyms of AMR in food crop value chains. Following two-stage screening, phenotypic results were extracted and categorized into primary and secondary combinations of acquired resistance in microbes of concern based on established prioritization. Occurrence of these pathogen-AMR phenotype combinations were summarized by sample group, value chain stage, and world region. Sub-analyses on antimicrobial resistance genes (ARG) focused on extended-spectrum beta-lactamase and tetracycline resistance genes. Results: Screening of 4455 citations yielded 196 studies originating from 49 countries, predominantly in Asia (89 studies) and Africa (38). Observations of pathogen-phenotype combinations of interest were reported in a subset of 133 studies (68%). Primary combinations, which include resistance to antimicrobials of critical importance to human medicine varied from 3% (carbapenem resistance) to 13% (fluoroquinolones), whereas secondary combinations, which include resistance to antimicrobials also used in agriculture ranged from 14% (aminoglycoside resistance) to 20% (aminopenicillins). Salad crops, vegetables, and culinary herbs were the most sampled crops with almost twice as many studies testing post-harvest samples. Sub-analysis of ARG found similar patterns corresponding to phenotypic results. Discussion: These results suggest that acquired AMR in opportunistic and obligate human pathogens is disseminated throughout food crop value chains in multiple world regions. However, few longitudinal studies exist and substantial heterogeneity in sampling methods currently limit quantification of exposure risks to consumers. This review highlights the need to include agriculturally-derived AMR in monitoring food safety risks from plant-based foods, and the challenges facing its surveillance.